Pengaruh Kualitas Produk Dan Variasi Produk Melalui Customer Experience Terhadap Minat Beli Sepeda Motor Yamaha: Studi Kasus Pada Konsumen Sepeda Motor Yamaha Di Desa Lubang Buaya Bekasi Timur - Angga Fathi Farahat; Hadita Hadita; Neng Siti Komariah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine whether Customer Experience can affect Product Quality and Product Variations on Buying Interest in Yamaha Motorcycle users in Lubang Buaya Village, East Bekasi. The method applied in this study is quantitative method. The sampling technique uses the Accidental Sampling technique. This research focused on Yamaha Motorcycles in Lubang Buaya Village, East Bekasi, with 105 respondents. Data analysis method techniques using statistical methods with SmartPLS 4.0 Software. The results of this study show that there are variables that influence each other, such as the following brief explanation: 1). Product Quality has a significant positive effect on Customer Experience, 2). Product Variations have a positive and significant effect on Customer Experience, 3). Customer Experience has a positive and significant effect on Buying Interest, 4). Customer Experience is able to fully mediate Product Quality against Buying Interest, 5). Customer Experience is able to fully mediate Product Variations on Buying Interest.